Evaluation of healthy lifestyle behaviors and the level of knowledge of cardiovascular risk factors of individuals 60 years old and older with a chronic disease - Nevzat Demirci; Ahmet Toptas (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: This study aimed to evaluate healthy lifestyle behaviors and levels of knowledge of cardiovascular risk factors of individuals with chronic diseases aged 60 and over. Material and methods: The study was conducted with 362 participants over the age of 60 (female 67.12 ± 5.11 and male 69.38 ± 5.51). The Cardiovascular Disease Risk Factors Knowledge Level (CARRF-KL) Scale and the Healthy Lifestyle Behaviors Scale II (HLBS II) were used in the study. Results: The total mean scores of the participants in CARRF-KL and HLBS II were 16.99 ± 4.69 and 105.17 ± 22.88, respectively. The mean scores of the spiritual development sub-dimensions of HLBS II were the highest, and the mean scores of the physical activity sub-dimensions were the lowest. There was a significant difference (p <0.05; **p <0.01) in CARRF-KL and HLBS II total scores and other sub-dimensions according to gender, marital status, smoking, education, income and chronic disease status. A positive, weak and statistically significant correlation (r = 0.316**, p <0.01) was found between CARRF-KL and HLBS-II. Conclusions: Increasing CARRF-KL and the development of HLBS II is thought to be an inevitable necessity for individuals 60 years old and older with a chronic disease to have a healthy lifestyle.